Beta-lactamases and detection of beta-lactam resistance in Enterobacter spp. - Pitout, J D (1997)
Enterobacter spp. are becoming increasingly frequent nosocomial pathogens, and beta-lactam-resistant strains are on the increase, especially among isolates recovered from intensive care units. Therefore, a study was designed to characterize the beta-lactamases produced by 80 isolates of E. cloacae, E. aerogenes, E. taylorae, E. gergoviae, E. sakazakii, E. asburiae, and E. agglomerans by induction studies, spectrophotometric hydrolysis assays, and isoelectric focusing. The ability of broth microdilution and disk diffusion susceptibility tests to detect resistance to 16 beta-lactam antibiotics among these species was also assessed. All species except E. agglomerans, E. gergoviae, and some isolates of E. sakazakii were found to produce a Bush group 1 cephalosporinase that was expressed inducibly or constitutively at high levels. In addition, some strains also produced a Bush group 2 beta-lactamase. In comparisons of broth microdilution and disk diffusion tests, disk diffusion tests failed to detect resistance in 1 of 25 isolates resistant to aztreonam and 2 of 30 isolates resistant to ceftazidime. These results indicate that species of Enterobacter can possess a variety of beta-lactamases that are responsible for beta-lactam resistance in this genus and that the disk diffusion test may occasionally miss resistance in some strains.